Diazotrophic activity and denitrification in two long-term chronosequences of maritime Antarctica - Perez, Cecilia A.; Kim, Mincheol; Aravena Donaire, Juan Carlos; Silva, Wladimir (My University, 2022)
The main goals of this study were to identify whether key processes involved in microbial soil nitrogen transformations, such as diazotrophic activity and denitrification, the chemical properties of limiting elements in the soil, and microbial community structure, differ in the different successional stages of two long term chronosequences in maritime Antarctica. Moreover, we expect the rates of diazotrophic activity and denitrification to be stimulated by increases in air temperature and moisture. To answer these questions, we selected three stages in the succession (early, mid and late) in each of two well established chronosequences: three raised beaches in Ardley Island; and the Barton Peninsula, which includes two cosmogenically dated sites and the forefield of the Fourcade glacier. In the Ardley chronosequence, higher diazotrophic activity was found in the older successional stages, concomitant with an increase in the abundance of Cyanobacteria. In the Barton chronosequence, Cyanobacteria were only present and abundant (Microcoleus) in the early successional stage, coinciding with the highest diazotrophic activity. Denitrification in the Barton chronosequence tended to be highest at the mid successional sites, associated with the highest abundance of Rhodanobacter. In the Ardley chronosequence, the lowest abundance of Rhodanobacter was linked to lower denitrification rates in the mid successional stage. In the Ardley chronosequence, significant positive effects of passive warming and water addition on diazotrophic activity were detected in the first and the second years of the study respectively. In the Barton chronosequence on the other hand, there was no response to either passive warming or water addition, probably a manifestation of the higher nutrient limitation in this site. Denitrification showed no response to either warming or water addition. Thus, the response of microbial nitrogen transformations to global change is highly dependent on the environmental setting, such as soil origin, age and climate regime.
Keywords: king george island; soil microbial communities; diazotrophs; denitrifiers